Australian sonographers' perceptions of patient safety in ultrasound imaging: Part 1 – identifying the main safety concerns, a qualitative study. (May 2023) - McInerney, John; Lombardo, Paul; Cowling, Cynthia; Roberts, Simone; Sim, Jenny
Introduction: Patient safety has been an undervalued component of quality healthcare but is a challenging area of research. Ultrasound is the most common imaging modality in the world. Research on patient safety in ultrasound is generally focused on bioeffects and safe operation of ultrasound equipment. However, other safety issues exist in practice that warrant consideration. This paper forms the first part of a PhD study exploring patient safety in medical diagnostic ultrasound, beyond the notion of bioeffects. The ultimate aim of the study is to inform the final phase of the research study which will consider the next steps in improving the quality and safety of healthcare experienced by patients. Methods: A qualitative study using semi-structured, one-on-one interviews. A thematic analysis categorised data into codes and generated final themes. Results: A heterogeneous mix of 31 sonographers, who reflected the profile of the profession in Australia, were interviewed between September 2019 and January 2020. Seven themes emerged from the analysis. These were bioeffects, physical safety, workload, reporting, professionalism, intimate examinations and infection control. Conclusion: This study presents a comprehensive analysis of sonographers' perceptions of patient safety in ultrasound imaging, not previously available in the literature. Consistent with the literature, patient safety in ultrasound tends to be viewed in technical terms through the potential for bioeffects of tissue damage or physical harm to the patient. However, other patient safety issues have emerged, and while not as well recognised, have the potential to negatively impact on patient safety.